Business Groups and Tunneling: Evidence from Private Securities Offerings by Korean Chaebols - BAEK, JAE‐SEUNG; KANG, JUN‐KOO; LEE, INMOO (Journal of Finance, 2006)
ABSTRACT We examine whether equity‐linked private securities offerings are used as a mechanism for tunneling among firms that belong to a Korean chaebol. We find that chaebol issuers involved in intragroup deals set the offering prices to benefit their controlling shareholders. We also find that chaebol issuers (member acquirers) realize an 8.8% (5.8%) higher (lower) announcement return than do other types of issuers (acquirers) if they sell private securities at a premium to other member firms, and if the controlling shareholders receive positive net gains from equity ownership in issuers and acquirers. These results are consistent with tunneling within business groups.